Morphological Investigations of Oxide Nanotubes Grown on Zircaloy-4 Cladding - Ali, G.; Shabbir, G.; Karim, S.; Khan, M.; Nisar, A.; Ahmad, M. (The Nucleus, 2016)
Self-organized, highly ordered and vertically oriented nanotubes have been fabricated on the surface of Zircaloy-4 (Zr-4) sheet using an electrochemical route. Anodization is carried out in ethylene glycol (EG) and glycerol electrolyte containing ammonium fluoride and de-ionized water. The morphology of nanotubes was studied using field emission scanning electron microscope (FESEM) and high resolution transmission electron microscope (HRTEM). Electron microscopy showed that self-organized nanotubes with regular ordered and extremely smooth wall morphology were obtained in glycerol based electrolyte. The diameter of the nanotubes could be tailored by anodization parameters. The TEM and SAED results revealed that the as-prepared nanotubes are closed at the bottom surface and have crystalline structure.